INTEGRATING EDMODO-BASED DIGITAL PORTFOLIO WITH EFL WRITING INSTRUCTION: EXPLORING THE STUDENTS’ PERCEPTIONS - Wahyu Kyestiati Sumarno; T. Tatik (Journal of English Education, 2018)
The increasing number of ICT integration into language classrooms has made many teachers conducted research to examine its effectiveness. Studies have shown that Edmodo is an effective tool for students to improve their writing skills. However, very few studies investigate the use of Edmodo as a media for digital portfolio and explore its impact in EFL writing classes. This research was done primarily aimed to describe EFL learners’ perceptions of the implementation of Edmodo-based digital portfolio in a Paragraph-based Writing course. Fifteen students participated in the study that lasted for seven meetings. Data were analyzed qualitatively and collected by using questionnaire and a semi-structured interview. Findings revealed that the students responded positively to the use of Edmodo-based digital portfolio in the writing course. Furthermore, they also reported that digital portfolio helps them improving their writing fluency and increasing self-reflection. This study recommends the use of Edmodo as a platform for an online portfolio in the writing class.